1999
DOI: 10.1152/ajprenal.1999.277.6.f957
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and subcellular immunolocalization of ClC-5 channel in mouse kidney: colocalization with H+-ATPase

Abstract: To determine the immunolocalization of ClC-5 in the mouse kidney, we developed a ClC-5-specific rat monoclonal antibody. Immunoblotting demonstrated an 85-kDa band of ClC-5 in the kidney and ClC-5 transfected cells. Immunocytochemistry revealed significant labeling of ClC-5 in brush-border membrane and subapical intracellular vesicles of the proximal tubule. In addition, apical and cytoplasmic staining was observed in the type A intercalated cells in the cortical collecting duct. In contrast, the staining was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
86
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(98 citation statements)
references
References 29 publications
6
86
1
Order By: Relevance
“…This disease is clinical relevant because of its major risk of evolution into uremia between the 3rd and 5th decades of life. ClC-5 is the first chloride channel for which a definitive role in the trafficking and acidification-dependent recycling of apical membrane proteins has been established (Gunther et al 1998;Devuyst et al 1999;Sakamoto et al 1999;Sayer and Simmons 2002). Animal models of knockout ClC-5 mice demonstrated that impairment of the endocytotic traffic is the major cause not only of tubular proteinuria but also of hypercalciuria and consequently kidney stones (Piwon et al 2000;Wang et al 2000;Gunther et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…This disease is clinical relevant because of its major risk of evolution into uremia between the 3rd and 5th decades of life. ClC-5 is the first chloride channel for which a definitive role in the trafficking and acidification-dependent recycling of apical membrane proteins has been established (Gunther et al 1998;Devuyst et al 1999;Sakamoto et al 1999;Sayer and Simmons 2002). Animal models of knockout ClC-5 mice demonstrated that impairment of the endocytotic traffic is the major cause not only of tubular proteinuria but also of hypercalciuria and consequently kidney stones (Piwon et al 2000;Wang et al 2000;Gunther et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…For ClC-4, which has mostly been reported to localize to endosomes (4,27) but also to the endoplasmic reticulum (ER) (28), an N-terminal amino acid stretch is reportedly involved in ER retention when expressed heterologously (28). The predominantly endosomal ClC-5 (4, 27, 29 -32), a small portion of which is endogenously found also in the plasma membrane (30,33), bears a C-terminal-located PY motif (34). Although not required for in vivo ClC-5 function (33), studies in Xenopus oocytes and cultured opossum kidney cells revealed that ubiquitin ligases bind this motif and ubiquitylate ClC-5, stimulating its internalization from the cell surface (34,35).…”
mentioning
confidence: 99%
“…This colocalization was seen in proximal tubules and in collecting duct intercalated cells, inside subcellular membrane vesicles. The presence of Cl -has been shown to support mechanisms leading to apical membrane insertion of these ATPases, as well as to filtered protein reabsorption (25)(26)(27). ClC3 and CFTR channels have also been implicated in this mechanism (2,28).…”
Section: Discussionmentioning
confidence: 99%